Antara Tradisionalisme dan Kemodernan: Pembelajaran Bahasa Arab Madrasah Minoritas Muslim Papua Barat - Ismail Suardi Wekke (TSAQAFAH, 2015)
Arabic language education is the compulsory subject of madrasah. Therefore, it shows there are many innovations to create joyful learning in fulfill students’ language competency. This article addresses the dynamic of Arabic teaching and learning in madrasah of Muslim minority environment. With its unique condition, it stimulates efforts to accelerate learning process in bridging the needs of community and class understanding. This article shows that there are three types Arabic language learning. Firstly, the classes were implemented curriculum model which formulated from government policy. Indeed, there are many determinations to enrich learning material to lengthen students’ competency. Secondly, the learning applied learning material that constructed through teacher experiences during pre-class observation. Furthermore, they accelerate the current condition through reading and grammar extension outside classroom. Finally, the combination between formal curriculum and textbook enlarge learning opportunity. These three types of experiences constructed due to institutional condition and objectives formulation. The Arabic teaching and learning is a pillar to support other subjects. Moreover, through the acceleration of subjects, Arabic is a foundation to maintain the acquisition of learning material. This article concludes that minority Muslim environment extend opportunities to learn Arabic. On the other hand, teachers and books constraint is not the main difficult. They solve those challenges through collaboration and innovation inter-institution.